Reproductive Conflicts in Cooperative Associations of Fire Ant Queens (Solenopsis invicta) - Bernasconi, Giorgina; Keller, Laurent (My University, 1996)
In ants, unrelated queens frequently associate to initiate a colony cooperatively. The joint reproductive effort of the cofoundresses increases growth and survival of the incipient colony. However, such associations are unstable. Soon after emergence of the first workers, queen-queen and queen-worker fights lead to the death or expulsion of all but one cofoundress. Because no sexual offspring are produced in incipient colonies the surviving queen monopolizes the entire future reproductive success of the colony. Two factors, the queens' relative fighting ability and their relative contribution to worker production (assuming that workers can recognize and selectively favour their mother) have been proposed to influence the survival prospects of individual queens within associations. The effect of these two factors was tested in the fire ant Solenopsis invicta. Initial size differences, a potential measure of the queens' fighting ability, affected the outcome of the conflicts, so that the initially heavier queen was more likely to survive. Differential loss of mass by initially equal nestmates also affected survival, with the queen losing more body mass being more likely to die. The manipulation of the queens' relative contribution to the worker brood did not significantly affect the queens' survival probability, suggesting that workers are unable to favour their mother.